2005
DOI: 10.1177/0095798405274720
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Values Among African-Descended Persons in the United Kingdom: Comparisons With European-Descended and Asian-Descended Persons

Abstract: In this study, conducted within the United Kingdom, the authors compared scores on five cultural values—namely, individualism, collectivism, familism, romanticism, and spiritualism—(a) between African-descended persons and European-descended persons and (b) between African-descended persons and Asian-descended persons. We predicted that African-descended persons would score higher than European-descended and Asian-descended persons on collectivism, lower than European-descended persons on individualism, and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Familialism reflects an orientation toward family relationships or a concern for the welfare of one's family (Gaines et al, 1997). Research has established familialism as a cultural value distinct from individualism and from romanticism (romantic partner orientation; Gaines et al, 1997;Gaines, Larbie, Patel, Pereira, & Sereke-Melake, 2005). Familial bonds are unlike dyadic connections and group belongingness; more specifically, they constitute a unique mixture (Kashima et al, 1995).…”
Section: Affirmation Of Familial Selfmentioning
confidence: 99%
“…Familialism reflects an orientation toward family relationships or a concern for the welfare of one's family (Gaines et al, 1997). Research has established familialism as a cultural value distinct from individualism and from romanticism (romantic partner orientation; Gaines et al, 1997;Gaines, Larbie, Patel, Pereira, & Sereke-Melake, 2005). Familial bonds are unlike dyadic connections and group belongingness; more specifically, they constitute a unique mixture (Kashima et al, 1995).…”
Section: Affirmation Of Familial Selfmentioning
confidence: 99%
“…Empirical research drawing from this conceptual base has identified a number of noteworthy antecedents and effects. For example, greater individualism has been shown to be associated with higher socioeconomic status (Marshall, 1997), urban residency (Freeman, 1997), and North American, Western European, or Australian acculturation (e.g., Gaines, Larbie, Patel, Pereira, & Sereke-Melake, 2005;Hofstede, 1980) and to lead to higher levels of entrepreneurial behavior (Morris, Davis, & Allen, 1994), stronger achievement values (Nelson and Shavitt (2002), and preferences for equitable, personalized rewards (Tower, Kelly, & Richards, 1997). Greater collectivism has been found to be associated with prior success working in groups or teams (Eby & Dobbins, 1997), and Asian, African, or South American acculturation (Gaines et al, 2005;Hofstede, 1980), and to lead to outcomes including stronger work group commitment (Clugston, Howell, & Dorfman, 2000), higher levels of citizenship behaviors (Moorman and Blakely, 1995;Van Dyne, Vandewalle, Kostova, Latham, & Cummings, 2000), and preferences for egalitarian team rewards (Kirkman & Shapiro, 2000).…”
Section: Team Member Individualism-collectivism and Performancementioning
confidence: 99%
“…Prior research suggests that individuals with a low collectivist orientation are likely to place great emphasis on achieving economic success and acquiring material resources, such as monetary rewards (see Gaines et al , 2005; Green et al , 2005). For example, Wagner and Moch (1986, p. 284) state that people with low collectivist orientations tend to “pursue only personal incentives, such as pay or praise that are personally beneficial and related to personal performance”.…”
Section: Theory and Hypothesesmentioning
confidence: 99%